The Paradox of an Unpolluted Coastal Site Facing a Chronically Contaminated Industrial Area - Corinaldesi, Cinzia; Bianchelli, Silvia; Rastelli, Eugenio; Varrella, Stefano; Canensi, Sara; Gambi, Cristina; Lo Martire, Marco; Musco, Luigi; Bertocci, Iacopo; Fanelli, Emanuela; Lucia, Giulia; Simoncini, Nicola; et al. (Frontiers in Marine Science, 2022)
Present and past industrial activities in coastal areas have left us a legacy of contamination and habitat degradation with potential implications for human health. Here, we investigated a coastal marine area enclosed in a Site of National Interest (SNI) of the central-western Adriatic (Mediterranean Sea), where priority actions of environmental remediation are required by governmental laws due the high environmental and human risk, and that is off-limits to any human activity since 2002. In particular, our investigation was focused on an area located in front of a chemical industry dismissed more than 3 decades ago. We report that the concentrations of heavy-metal and organic contaminants in the investigated sediments were generally lower than those expected to induce detrimental biological effects. Meiofaunal abundance, biomass and community structure changed among stations, but regardless of the distance from the abandoned industrial plant. Taxa richness within the SNI did not change significantly compared to the controls and the lack of some taxa in the SNI transects was not due to the contamination of the SNI area. The results of this study suggest a natural recovery of the marine area over 2 decades of restrictions on human activities, including fishing and shipping bans. If the hypothesis of the natural recovery of this SNI will be further confirmed by other studies, the plans for the identification and monitoring of the most polluted areas in Italy should necessarily be redefined also in the light of the Water Framework, the Marine Strategy Framework and the Environmental Quality Standard Directives.